2020
DOI: 10.1042/bsr20193431
|View full text |Cite|
|
Sign up to set email alerts
|

Naringin protects endothelial cells from apoptosis and inflammation by regulating the Hippo-YAP Pathway

Abstract: Atherosclerosis is the primary cause of several cardiovascular diseases. Oxidized low-density lipoprotein (ox-LDL)-induced apoptosis, endothelial–mesenchymal transition (EndMT), and inflammation are crucial for the progression of cardiovascular diseases, including atherosclerosis. Naringin, a major compound from tomatoes, grapefruits, and related citrus, reportedly exhibits potential protective effects during atherosclerosis development; however, its effect on ox-LDL-induced human umbilical vein endothelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 28 publications
2
56
0
Order By: Relevance
“…In pulmonary hypertension, EndMT causes matrixgenerating fibroblasts and contributes to the progression of extracellular matrix productions and collagen depositions, and subsequently causes the pulmonary vascular remodeling (Xiong, 2015). Naringin are found to produce protective effects against End MT in atherosclerosis (Zhao et al, 2020). Here in this study, our data indicated significantly decreased endothelial markers, increased mesenchymal markers, and EndMT-related transcription factors in the lung tissue of an MCT-induced rat model of PAH.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In pulmonary hypertension, EndMT causes matrixgenerating fibroblasts and contributes to the progression of extracellular matrix productions and collagen depositions, and subsequently causes the pulmonary vascular remodeling (Xiong, 2015). Naringin are found to produce protective effects against End MT in atherosclerosis (Zhao et al, 2020). Here in this study, our data indicated significantly decreased endothelial markers, increased mesenchymal markers, and EndMT-related transcription factors in the lung tissue of an MCT-induced rat model of PAH.…”
Section: Discussionsupporting
confidence: 59%
“…Naringin is a flavanone glycoside synthesized from the flavanone naringenin and the disaccharide neohesperidose. Previous studies have demonstrated the potential protective effects of Naringin on diseases including osteoporosis, atherosclerosis, hypertension, and alcoholic hepatic steatosis (Zhao et al, 2020;Akintunde et al, 2020;Zhou et al, 2019). However, the efficacies of Naringin to the pathogenesis of PAH is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naringin, a polymethoxylated flavonoid glycoside, is the main bioactive flavonoid extracted from citrus fruits [ 6 , 7 ] and has a positive effect on osteoporosis caused by postmenopause, glucocorticoid, orchidectomy, and aging [ 8 ]. Studies have shown that naringin can promote the differentiation and proliferation of various types of cells [ 9 – 12 ] and improve the bone mass in an osteoporotic rat model [ 9 ]. Naringin also promotes osteoclast apoptosis through the mitochondrial-mediated apoptotic pathway, so as to inhibit bone loss in OVX rat models and exhibit antiosteoporotic pharmacological activity [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inactivated Hippo pathway rarely could make phosphorylation to YAP protein. The unphosphorylated YAP protein enriches in the nucleus via translocating into the nucleus to promote the expression of related genes that contribute to cell proliferation and survival [8]. Therefore, the activation of Hippo pathway determines the phosphorylation level and subcellular localization of YAP protein, which also determines the role of this pathway in tumorigenesis and development.…”
Section: Introductionmentioning
confidence: 99%